Theta burst stimulation over the prefrontal cortex: Effects on cerebral oximetry and cardiovascular measures in healthy humans. (1st May 2021) - Pinto, Nuno; Gonçalves, Helena; Silva, Ricardo; Duarte, Marta; Gama, Jorge; Vaz Pato, Maria
Highlights: Left hemisphere cTBS originated a significant reduction in frontal cortex oximetry. Right hemisphere cTBS originated a significant reduction of systolic mean pressure. TBS seems to influence both oximetric measures and autonomic dependent responses. Abstract: Theta Burst Stimulation (TBS) is a non-invasive neurophysiological technique, able to induce changes in synaptic activity. Research suggests that TBS may induce changes in cerebral oxygenation, cerebral blood flow, blood pressure and heart rate but there are conflicting results across studies. Thus, the objective of our sham-controlled study is to evaluate if TBS applied to the dorsolateral prefrontal cortex (DLPFC) of healthy volunteers produces changes in cerebral oximetry, heart rate and blood pressure. Forty-nine volunteers of both sexes were randomly allocated to one of five stimulation groups. Before and after real TBS or sham stimulation, blood pressure, heart rate, and cerebral oxygenation of the volunteers were measured. Cerebral oxygenation values were obtained with a near infra-red spectroscopy system. We found a significant reduction in left cortex oximetry after continuous TBS (cTBS) over the left DLPFC (p = 0.039) and a non-significant reduction in right cortex oximetry (p = 0.052). Right hemisphere inhibition (using cTBS) seemed to originate a significant reduction of 8 mmHg in systolic arterial pressure. No other changes were seen in oximetry, cardiac frequency and diastolic arterial pressure. In our group of normal subjects, cTBS applied to the left DLPFC was able to reduce oxygenation in the left cortex. Right hemisphere inhibition was associated with a significant reduction in systolic pressure.